2018
DOI: 10.1037/sah0000103
|View full text |Cite
|
Sign up to set email alerts
|

The mediating effect of social support on the relationship between the impact of experienced stigma and mental health.

Abstract: The impact of stigma and discrimination against persons with mental illness is well documented. Less well researched are the interpersonal and intrapersonal mechanisms that mediate how acts of discrimination impact persons with mental illness, specifically social support. Past research has focused on the buffering, or moderating impact of perceived social support. We hypothesize that perceived social support is a psychological process, changed by interactions with the outside world, including stressful interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 57 publications
(82 reference statements)
2
27
0
Order By: Relevance
“…Our findings support the social causation model, which theorizes that experiencing discrimination damages social connections, leading to heightened psychological distress [9,10]. Other studies have also identified that race-based and mental illness-based discrimination had indirect effects on mental health outcomes through social support [10,46,47]. Although no studies to our knowledge have tested this model among HCWs, qualitative studies have identified that minority and female HCWs face discrimination in terms of social exclusion and isolation [30,48] that could prevent them from accessing the mental health benefits of social support.…”
Section: Discussionsupporting
confidence: 83%
“…Our findings support the social causation model, which theorizes that experiencing discrimination damages social connections, leading to heightened psychological distress [9,10]. Other studies have also identified that race-based and mental illness-based discrimination had indirect effects on mental health outcomes through social support [10,46,47]. Although no studies to our knowledge have tested this model among HCWs, qualitative studies have identified that minority and female HCWs face discrimination in terms of social exclusion and isolation [30,48] that could prevent them from accessing the mental health benefits of social support.…”
Section: Discussionsupporting
confidence: 83%
“…There is emerging clinical evidence that values-clarification can be beneficial in the face of racism (West, Graham, & Roemer, 2013), though this has not been examined among individuals experiencing mental health problems or severe mental illness and is an important question for future study. In addition, building positive social relationships with individuals who share similar marginalized experiences and identities may also promote resilience, and positive mental health in the face of dual stigmatization (Kondrat, Sullivan, Wilkins, Barrett, & Beerbower, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…According to the socalled social buffer hypothesis (Cohen and McKay 1984), negative effects of stressors on health and well-being are reduced or even eliminated by receiving social support from social ties. This hypothesized moderation effect has been empirically found in multiple studies across various contexts (Barth et al 2010;Bowen et al 2014;Cohen and Wills 1985;Earnshaw et al 2015;Holtfreter et al 2017;Holt-Lunstad et al 2010;Kondrat et al 2017;Matos et al 2017;Thoits 1995Thoits , 2011Uchino 2004Uchino , 2009). Social support could be influential in the relation between health problems and employment by providing different types of social support.…”
Section: The Protective Effect Of Close Social Tiesmentioning
confidence: 77%